2020
DOI: 10.1111/inr.12641
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students learning to care for refugee patients: a qualitative study

Abstract: Background Nursing students should gain cultural knowledge and skills necessary for providing care to all types of patients. Aim This study aimed to determine problems faced by nursing students who care for refugee patients. Method The study used phenomenological qualitative design. The sample comprised 25 nursing students who cared for refugee patients in a clinic. Data were analysed using Colaizzi’s seven‐step method following focus group interviews. Results Two themes were identified for the interviews: (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In that case study, similar to our results, all of the healthcare staff faced communication difficulties and problems with the availability of interpreters (Chang et al, 2014). Evgin and Muz (2021) examined nursing students' experiences in caring for refugee patients through a phenomenological study. In that study, 25 nursing students who cared for refugee patients were interviewed, and they emphasized that language barriers negatively affect care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case study, similar to our results, all of the healthcare staff faced communication difficulties and problems with the availability of interpreters (Chang et al, 2014). Evgin and Muz (2021) examined nursing students' experiences in caring for refugee patients through a phenomenological study. In that study, 25 nursing students who cared for refugee patients were interviewed, and they emphasized that language barriers negatively affect care.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 25 nursing students who cared for refugee patients were interviewed, and they emphasized that language barriers negatively affect care. They also reported that patient education could not be provided because of language problems and superficial communication (Evgin & Muz, 2021). The results of another qualitative study conducted in Turkey examined senior nursing students' experiences in caring for refugee patients and similarly showed that language and communication are the biggest problems encountered while providing care (Karakuş Selçuk & Yanikkerem, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses demand training in compassion, cultural competencies, and human trafficking (Albright et al, 2020;Dumit & Honein-AbouHaidar, 2019). This would also be useful for students learning about UM care (Evgin & Muz, 2020). As other studies demonstrate (Harrison & Daker-White, 2019), participants propose having more time to provide care, promoting clinical autonomy, exploring stigma, defending patients (UMs) and safeguarding the care history of UMs as ways to improve the issue (Chiarenza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of this competence must be continuous, it should begin with entrance into the nursing education programme and be spread across the curriculum, i.e. during undergraduate nursing‐degree studies (Choi & Kim, 2018; Evgin & Muz, 2020; Markey & Okantey, 2019).…”
Section: Introductionmentioning
confidence: 99%